Persepsi Mahasiswa Terhadap Media Pembelajaran Google Meet dan Liveworksheet.com dalam Mata Kuliah Bahasa Inggris - Ningrum, Desi Innanti Wicaya (Neolectura, 2025)
Digital learning platforms are currently still being used in various educational institutions, one of institution is Politeknik Sawunggalih Aji which still maintains the use of digital learning platforms as a means in certain learning processes that cannot be carried out face-to-face for special reasons. One example is the acceptance of a student with a disability who is unable to attend lectures face-to-face. Since there is only one disabled student in the Digital Business study program, the student is included in the regular learning class. The platforms used to connect this student are Google Meet and Liveworksheet.com. This research is a qualitative research with the aim of knowing the perceptions of students with disabilities in using Google Meet and Liveworkshet.com. Respondent was consisted of one student with a disability who was unable to attend face-to-face meetings. The results of this study are positive perceptions regarding the Internet network and positive perceptions in terms of effectiveness when using Google Meet. Then for the use of Livewoksheet.com, it is concluded that there is a positive perception of the effectiveness and variety of working on exercise or evaluation questions.